(untitled) (Jurnal Adabiya, 2020)
OPAC is an information-based information technology back-up system that can be accessed online. This study aims to determine the availability of OPAC as a service of information retrieval in Taman Baca FISIP UNSYIAH. The research method use is case study. Tchnique of collecting data using observation and interview. The result of research that the application of OPAC in Taman Baca Fisip Unsyiah not yet maximal, the role of librarian, facilities and infrastructure must be improved